Mapping the landscape of psychological contract literature: a scopus-based bibliometric analysis - Wu, Hao; Subramaniam, Anusuiya; Rahamat, Syafiqah (RMP Publications, 2023)
The employment relationship between employees and organizations has changed with the advent of the knowledge economy era in the 21st century and the transformation of economic models. Psychological contracts are significant in understanding the employment relationship between employees and organizations. More and more scholars began to focus on psychological contracts. Therefore, the systematic arrangement of psychological contract literature is meaningful. This study used bibliometrics to review 2,097 articles and conference papers from psychological contracts. The Scopus database is the source of literature collection in this study. This study used VOSviewer and Microsoft Excel for the bibliometric analysis of these documents. Firstly, this study summarized the temporal trends and primary sources of psychological contracts. This study found an exponential increase in publications and a Matthew effect in sources of psychological contracts. Secondly, eight major co-authorship groups were found and discussed the significant contributions made by these scholars to psychological contract theory. Thirdly, this study also analyzed the countries, affiliations, funding sponsors, and subject areas of the psychological contract. Finally, the hot topic of psychological contracts and suggested future research were discussed. This study systematically summarized the literature on the psychological contract and future research direction.